2020
DOI: 10.2166/ws.2020.307
|View full text |Cite
|
Sign up to set email alerts
|

Water saving potential and economic viability assessment of rainwater harvesting system for four different climatic regions in China

Abstract: Rainwater is one of the most promising alternative water sources. However, the financial outcomes of the rainwater harvesting systems are not always assured due to the economic performance of RWH system varies greatly under different climatic conditions.This paper investigates reliability,water saving and benefit cost ratio of RWH system with different storage tanks and under three distinct climatic conditions (i.e.,wet, average and dry year) at four cities in China. It is found that for a standard building (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…For example, for an 8-story office building with a roof area of 1600 m 2 and 500 occupants in the Guangzhou area (with an average annual precipitation of 1790 mm), the AWS reach 2000 m 3 , accounting for approximately 33% of the total water consumption of the building throughout the year. When the storage volume is optimized, the unit construction cost of the RWH system is 2.62 CNY/m 2 and the dynamic payback period is 12.1 years (Shiguang & Yu, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, for an 8-story office building with a roof area of 1600 m 2 and 500 occupants in the Guangzhou area (with an average annual precipitation of 1790 mm), the AWS reach 2000 m 3 , accounting for approximately 33% of the total water consumption of the building throughout the year. When the storage volume is optimized, the unit construction cost of the RWH system is 2.62 CNY/m 2 and the dynamic payback period is 12.1 years (Shiguang & Yu, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The specific formula of the daily rainfall–water balance model is shown in eqn (2) and (3): Q t = P t + V t −1 − D where P t = ρ × H × A − FFLwhen Q t < 0, V t = 0;when Q t > C , V t = C ;where Q t is the cumulative water stored in the rainwater tank (m 3 ) after the end of the t th day, P t is the harvested rainwater (m 3 ) on the t th day, V t −1 is the storage in the tank (m 3 ) at the end of the ( t − 1)th day, D is the daily rainwater demand (m 3 ), ρ is the runoff co-efficient (0.9), H is the daily rainfall (mm), A is the roof area (m 2 ), and FFL (first flash loss) is considered to be 150 L. If Q t −1 > FFL, then FFL for day ‘ t ’ is computed to be 10% only (15 L). 15 C is the capacity of the rainwater tank (m 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…This result is similar to a recent study by Chen and Zhang who found that climate change variabilities for expected water savings are more significant in Guangzhou and Harbin than those in Wuhan and Beijing. 15 To sum up, when adopting RHSs, each region can comprehensively consider local water consumption, water saving benefits and climate change impact to formulate an appropriate rainwater utilization strategy.…”
Section: Rainwater Utilization Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic criteria should incorporate issues such as distance from settlements, family size, education level and water price, which can improve the RWH effectiveness (Pavolová et al 2019) while at the same time allowing for the planning of future structures. Furthermore, other factors such as funding and government subsidies (Fernandes et al 2020;Shiguang & Yu 2021) can make the RWH economically viable. Nevertheless, the establishment of good socioeconomic indicators associated with RWH system performance is much more difficult for socioeconomic conditions than for technical conditions (Adham et al 2018).…”
Section: Introductionmentioning
confidence: 99%